PERAN MAHASISWA DALAM ERA DIGITALISASI PENDIDIKAN ISLAM: ADAPTASI, INOVASI, DAN TANGGUNG JAWAB - Khubni Maghfirotun (Rihlah Review: Jurnal Pendidikan Islam, 2025)
The era of digitalization has brought about significant transformations in various sectors, including Islamic Education. This study aims to analyze the role of students in the Islamic Education study program at the Faculty of Islamic Religion, Universitas Billfat, in navigating the digitalization of Islamic Education, focusing on their adaptation, innovation, and responsibilities. Employing a descriptive qualitative approach with a case study method, data were collected through in-depth interviews and online questionnaires from students of the Islamic Education study program at the Faculty of Islamic Religion, Universitas Billfath. The findings indicate that students adapt by utilizing online learning platforms and digital learning resources, and they innovate through the creation of educational content and the utilization of social media for da'wah. Furthermore, students demonstrate a growing awareness of digital ethical responsibilities, including caution in disseminating information and upholding Islamic values. In conclusion, students of the Islamic Education study program at the Faculty of Islamic Religion, Universitas Billfat, are key agents in the transformation of Islamic Education in the digital age, requiring support from educational institutions through digital literacy training and innovation facilitation. Keyword: Islamic Education; Digital Era; Student Role; Adaptation; Innovation; Responsibility; Islamic Religious Education; Universitas Billfath.